Ritual Besawai-Bapelas sebagai Sarana Pelestarian Nilai Kebersamaan pada Masyarakat Adat Guntung, Bontang Kalimantan Timur - Putri Handayani; Moh Bahzar; Asnar Asnar; Alim Salamah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
Indonesia’s cultural diversity is reflected in the rich traditions of its indigenous communities, which function not only as spiritual expressions but also as mechanisms for maintaining social cohesion. However, modernization and changing lifestyles have increasingly challenged the sustainability of local traditions. This study aims to analyze the role of the Besawai–Bapelas ritual as a medium for preserving the values of togetherness and social solidarity within the Urang Kutai community of Kampung Adat Guntung, Bontang City, East Kalimantan. This research employs a qualitative approach using in-depth interviews with the head of adat and community members selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model, with triangulation applied to ensure data validity. The findings indicate that the Besawai–Bapelas ritual serves as a social glue that strengthens collective identity, reinforces solidarity, and sustains cultural continuity across generations. In conclusion, Besawai–Bapelas plays a vital role not only as a sacred tradition but also as a cultural strategy for maintaining social cohesion amid ongoing social change.